Respuesta :
Answer:
x = 7
Step-by-step explanation:
Given
7x + 4(- 3x + 6) = - 7x + 38 ← distribute and simplify left side
7x - 12x + 24 = - 7x + 38
- 5x + 24 = - 7x + 38 ( add 7x to both sides )
2x + 24 = 38 ( subtract 24 from both sides )
2x = 14 ( divide both sides by 2 )
x = 7
Answer:
Step-by-step explanation:
Here you go mate
Use PEMDAS
Parenthesis
Exponent
Multiplication
Division
Addition
Subtraction
Step 1
7x+4(-3x+6) =-7x+38 Equation/Question
Step 2
7x+4(-3x+6) =-7x+38 Remove parenthesis
-5x+24=−7x+38
Step 3
-5x+24=−7x+38 Add 7x
2x+24=38
Step 4
2x+24=38 Subtract 24
2x=14
Step 5
2x=14 Divide by 2
answer
x=7
Hope this helps